2021
DOI: 10.18502/jfsh.v6i4.7566
|View full text |Cite
|
Sign up to set email alerts
|

Low dose irradiation of plum peel anthocyanins: Impact on stability and antioxidant activity

Abstract: Consumer demand for both natural food colorants and non-thermal methods of preservation has increased overwhelmingly during the last few decades. Preventing loss of appeal and color through non-thermal methods without compromising on quality will provide an alternative to conventional thermal methods. In the present study, irradiation of plum peel anthocyanins after extraction and purification was done in a range of 0.1-1.0 kGy. Results revealed that degradation was significantly (p ≤ 0.05) dependent on both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Koulani et al. (2016) have also concluded that the furfural content in anthocyanin samples containing sucrose is higher than the samples without sucrose.…”
Section: Resultsmentioning
confidence: 95%
“…Koulani et al. (2016) have also concluded that the furfural content in anthocyanin samples containing sucrose is higher than the samples without sucrose.…”
Section: Resultsmentioning
confidence: 95%